Elaboración de modelos univariados de series de tiempo para la estimación y pronóstico de las tasas de redimiento del patrimonio y del pasivo de la caja municipal de ahorro y crédito de Arequipa periodo 2002 - 2020 - Vargas Pinedo, Daniel Paolo (2021)
The microfinance market fulfills the function of providing and allowing the participation of economic agents that do not have the necessary conditions to obtain financial instruments granted by conventional financial entities such as banks. In this way, microfinance institutions seek to satisfy these unmet needs by promoting opportunities such as lines of credit or deposits, with less restrictive requirements. Given this perspective, this thesis seeks to investigate and analyze the development and evolution of two pillars that frame the financial situation of a representative agent of this market, which is the Caja Municipal de Ahorro y Crédito de Arequipa. study variables to the total liabilities and the total equity of the same entity and will seek to study the behavior of the respective rates of return to said variables, taking as the study time frame the months that are between the years 2002 to 2020. Likewise, the necessary econometric techniques will be carried out guided by the analytical panorama of time series, therefore, in this way it will be possible to formulate and evaluate different sections that will guarantee an adequate estimate for each of the rates of return, achieving validation in a first instance the stationary behavior of the same until explaining what is the expected behavior of these rates by means of the elaboration of forecasts for the five months following the analysis period.